Burnout among diabetes specialist registrars across the United Kingdom in the post-pandemic era - Agha, Adnan; Basu, Ansu; Anwar, Eram; Hanif, Wasim (Frontiers in Medicine, 2024)
Introduction: Burnout syndrome is a condition resulting from chronic work-related stress exposure and can be identified by the presence of one or more of the three classic dimensions of burnout, i.e., emotional exhaustion, depersonalization, and lack of personal accomplishment, which negatively impact physician health and productivity. Objective: This study aimed to identify burnout among Diabetes and Endocrinology Specialty Training Registrars (DStRs) across the United Kingdom. Design/Setting: It was a Cross-sectional observational study after ethical approval (ERSC_2022_1166), utilizing the gold standard Maslach Burnout Inventory to measure burnout syndrome, and to determine self-reported stressors and compare them with the results of our previous survey in 2018. Participants: Over 430 DStRs across the United Kingdom were invited electronically through their deanery representatives and specialty training bodies. Results: Using Google Forms™ to gather data, we were able to collect 104 completed surveys. Results revealed that 62.5% (n = 65) of participants have burnout (5% increase from the previous survey in 2018), 38.6% (n = 40) have high emotional exhaustion, and 44.2% (n = 46) feel a lack of personal accomplishment. “General Internal Medicine specific workload” was the most common self-reported stressor reported by 87.5% (n = 91) of participants, whereas bullying/harassment and discrimination at work were reported by 35.6% (n = 37) and 30.77% (n = 32) of participants, respectively. Using multivariable logistic regression model, personal stress (OR, 4.00; 95% CI, 1.48–10.86; p = 0.006) had significant, while Bullying/harassment (OR, 3.75; 95% CI, 0.93–15.12; p = 0.063) had marginal impact on the presence of burnout. Conclusion: Diabetes and Endocrinology Specialty Training Registrars frequently experience burnout syndrome, which has increased over the last 4 years. However, organizational changes can help identify, prevent, and treat physician burnout.